2015
DOI: 10.1186/s13071-015-0778-5
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and genetic characterization of Toxoplasma gondii in cancer patients in Anhui Province, Eastern China

Abstract: BackgroundRecent studies have indicated the predominance of Toxoplasma gondii genotype Chinese 1 in animals in China. However, little is known of the genetic features of the parasite in humans. This study aims to determine the prevalence of anti-T. gondii antibodies based on which the genetic character of the parasite was identified in cancer patients in China.MethodsA total of 1014 serum samples with malignant neoplasms were collected from six tertiary-care hospitals (HAUCM, APH, HAMU, XAH, FHH and HBMC) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 37 publications
5
42
0
1
Order By: Relevance
“…These results suggested higher prevalence than that of Wang et al who reported 8.96% prevalence of antibodies to T. gondii in male cancer patients and 7.45% in females. These findings could be due to the geographical variation and genetic susceptibility [15]. As the functions of the immune system are disturbed in patients with aneoplasm [16], toxoplasmosis has been described in association with some malignancies [13].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested higher prevalence than that of Wang et al who reported 8.96% prevalence of antibodies to T. gondii in male cancer patients and 7.45% in females. These findings could be due to the geographical variation and genetic susceptibility [15]. As the functions of the immune system are disturbed in patients with aneoplasm [16], toxoplasmosis has been described in association with some malignancies [13].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly one-third of the world's population is thought to be infected with this parasite [2]. The prevalence rate of T. gondii in China is over 7% and this rate is constantly rising due to the rapid growth of the number of cats (pet and stray cats) [3][4][5]. This parasite has three infective forms: the tachyzoite, the bradyzoite inside tissue cysts and the sporozoite in sporulated oocyst [6].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients who are seronegative for T. gondii infection could benefit from advice on precautionary measures, to avoid seroconversion that may induce active severe toxoplasmosis [15]. Therefore, potential associations between T. gondii infection and cancer have attracted a lot of attention [3,4,[16][17][18][19][20][21][22][23][24][25][26]. Oral cancer is one of the most common malignant tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Also it showed the presence of severe infection in some samples with toxoplasmosis and cancer patients. The presence of acute infection in previous studies mentioned above due to the nature of the studied groups some of them were members of the workers in the massacres, and the other were pregnant women while the rest were couples as well as other samples were randomly taken, especially pregnant women and those were workers in the massacres which is exposed to risk factors from workers who could be infected with acute toxoplasmosis in the current study, the presence of severe infection consistent with both Nimir and others (2015), [7] and Wang et al;, [8] who pointed to the existence of severe infection toxoplasmosis among patients of cancer and in spite of the presence of acute infection. Those patients did not show 1365 symptoms of toxoplasmosis.…”
Section: Ca19-9mentioning
confidence: 57%
“…Those patients did not show 1365 symptoms of toxoplasmosis. The severe infection among these patients due to the low level and the efficiency of the immune system have as a result of cancer and receiving chemotherapy, making them susceptible to many diseases, including toxoplasmosis, especially in the event of exposure to risk factors such as during water contaminated food and eating or contact with cats or dealing with contaminated materials infectious those phases of the parasite (meat, dust and other) (Mahammad and others, 2012; Wang et al, 2015) [8,9]. Khudair (2012) [10] and Kalantari ,N. et al; [11] .…”
Section: Ca19-9mentioning
confidence: 99%